Peran Rangkap Jabatan Dalam Peningkatan Kinerja Organisasi Pada PT Mustika Karya Anugrah Surabaya - Usfatun Khasanah; Nanang Sutedja; Asep Saepuloh (Jurnal Mahasiswa Manajemen, 2022)
Background - In 2020 the organizational performance of PT Mustika Karya Anugrah decreased because there were two employees who held concurrent positions. However, in 2022 the company's performance increased even though there were several employees who played multiple roles. This is evidenced by the achievement of five performance indicators. Objective - The purpose of this study was to determine the role of concurrent positions in improving organizational performance at PT Mustika Karya Anugrah Surabaya which is engaged in the importer-distributor of fruit. Design/Methodology/Approach - This research is qualitative research using primary data and secondary data. Data collection techniques in this study were through interviews and observations. The selection of informants in this study was carried out using purposive sampling method. Findings - The results of this study indicate that organizational performance at PT Mustika Karya Anugrah Surabaya will increase in 2022 even though some of its employees have to work concurrently. This is because good leadership and internal control systems have been implemented by the company. All employees who hold concurrent positions or do not hold concurrent positions can complete their duties properly. Increased organizational performance is evidenced by increased company productivity, good service quality results in customer satisfaction, the achievement of responsiveness, responsibility, and accountability. Research implications - This research contributes to the trap of position in order to maintain a sense of belonging to the company by not expecting large compensation or rewards from the company, the trap of position accepting assignments with the aim of advancing the company. Research limitations - This research is only conducted on employees who carry out dual roles at PT Mustika Karya Anugrah Surabaya.